2011
DOI: 10.2519/jospt.2011.3488
|View full text |Cite
|
Sign up to set email alerts
|

Fear-Avoidance Beliefs and Clinical Outcomes for Patients Seeking Outpatient Physical Therapy for Musculoskeletal Pain Conditions

Abstract: Study Design Prospective cohort. Objective To investigate fear-avoidance eliefs across different anatomical regions for patients with musculoskeletal pain. Background Fear-avoidance beliefs were first widely studied in patients with low back pain. The early results of studies involving patients with cervical spine, knee, and shoulder disorders suggest that fear-avoidance beliefs have the potential to influence pain and function in different anatomical regions. However, very few prospective studies of fear-avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 30 publications
6
79
2
2
Order By: Relevance
“…As summarized by George et al, 19 when using the complete FABQ-PA, there is evidence indicating that elevated fear-avoidance beliefs can be predictive of poor outcomes for patients with lumbar spine dysfunctions. 12,15,56 In addition, George and Stryker 18 reported that when dichotomizing patients of cervical, upper extremity, lumbar or lower extremity musculoskeletal pain using the psychometric methods described by Hart et al, 29 FABQ-PA was associated with functional outcomes, although patients with elevated FABQ-PA were associated with more functional change compared to those with not-elevated FABQ-PA. In our multivariable model, fear-avoidance added little to our understanding of FS outcomes, so we conducted a univariate analysis using the same data set.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As summarized by George et al, 19 when using the complete FABQ-PA, there is evidence indicating that elevated fear-avoidance beliefs can be predictive of poor outcomes for patients with lumbar spine dysfunctions. 12,15,56 In addition, George and Stryker 18 reported that when dichotomizing patients of cervical, upper extremity, lumbar or lower extremity musculoskeletal pain using the psychometric methods described by Hart et al, 29 FABQ-PA was associated with functional outcomes, although patients with elevated FABQ-PA were associated with more functional change compared to those with not-elevated FABQ-PA. In our multivariable model, fear-avoidance added little to our understanding of FS outcomes, so we conducted a univariate analysis using the same data set.…”
Section: Discussionmentioning
confidence: 99%
“…Change in fear during therapy might prove a stronger predictor of FS outcomes compared to fear level at intake, as has been suggested. 62 Regardless of the FS outcomes measure, 15,18,25 assessing the level of fear-avoidance beliefs at initial evaluation for patients with lumbar spine dysfunctions seems warranted, particularly if evaluation results are used to develop targeted interventions that are used to assist in patient management for improved functional outcomes. Therefore, we recommend that clinicians use methods like the one described here to identify patients with elevated fearavoidance beliefs and decide whether to use targeted interventions for those with elevated fear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient's fear of performing tasks and cervical movements was assessed using the Fear-Avoidance Beliefs Questionnaire (FABQ). 9,26,37 This questionnaire consists of 16 questions and focuses on pain-related fear of movement during physical activities (FABQPA) and work (FABQW). Although not as extensively documented, the FABQ has adequate psychometric properties.…”
Section: 48mentioning
confidence: 99%